2021
DOI: 10.1111/ijcp.14338
|View full text |Cite
|
Sign up to set email alerts
|

Rectal spacers in patients with prostate cancer undergoing radiotherapy: A survey of UK uro‐oncologists

Abstract: Radical radiotherapy and brachytherapy are recommended in guidelines for the management of patients with localised or locally advanced prostate cancer. 1,2 However, the prostate is a mobile structure, 3 which means that movement during focal treatments can increase the field of exposure, including the rectum and bladder, resulting in potentially serious toxicities.Bowel toxicities include urgency, loose stools, increased frequency of bowel movements, rectal bleeding and faecal incontinence, which can all impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…A questionnaire sent to urologists within the United Kingdom indicated that only 37% of surgeons had inserted a rectal spacer, despite 68% saying that they would be open to using them in the future. 21 Furthermore, most of those who had inserted spacers before had used them within the private sector or for those with pre-existing bowel conditions. This is forcing many patients to apply to the private sector to get a spacer or to travel long distances to undergo spacer insertion in the public health service.…”
Section: Use Of Spacers Within the United Kingdommentioning
confidence: 99%
“…A questionnaire sent to urologists within the United Kingdom indicated that only 37% of surgeons had inserted a rectal spacer, despite 68% saying that they would be open to using them in the future. 21 Furthermore, most of those who had inserted spacers before had used them within the private sector or for those with pre-existing bowel conditions. This is forcing many patients to apply to the private sector to get a spacer or to travel long distances to undergo spacer insertion in the public health service.…”
Section: Use Of Spacers Within the United Kingdommentioning
confidence: 99%